ANALISIS FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK PELAKU UMKM DI KECAMATAN PLAYEN KABUPATEN GUNUNGKIDUL - Ika Wulandari; Vera Y Sinaga, Yuliana; Bayu Utomo , Rochmad (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This study aims to determine the factors that influence taxpayer compliance for SMEs in the Playen District, Gunungkidul Regency. The research method used is quantitative research methods. The data source used is primary data. The population in this study is the Taxpayer of SMEs in the District Playen Gunungkidul District with a total sample of 183 respondents. The data analysis technique used is multiple linear regression analysis. The results showed that tax knowledge and quality of fiscal services partially had a positive effect on tax compliance of SMEs in the District of Playen, Gunungkidul.